Kecemasan Karir Mahasiswa Sarjana dan Mahasiswa Vokasi - Muhdi Agung, Qusuma Astuti; Nur’Aini, Siti; Wibowo, Danan Satriyo (Indonesian Journal Publisher, 2024)
Career anxiety is a feeling felt by individuals regarding worry, confusion, and doubt regarding the right career continuation for themselves. Career anxiety reflects a situation where individuals experience difficulty in making decisions regarding career choices, due to the complexity of factors that influence each other in the decision-making process. This research aims to differentiate the level of career anxiety between undergraduate students and vocational students. The type of research used is non-experimental quantitative research with comparative methods. The population in this study was 63,219 undergraduate and vocational students from 4 state and private universities in Jember with a sample of 397 students. The sampling technique uses quota sampling. The scale used is the Career Anxiety Scale (CAS) consisting of 12 items adapted from Thai, et al (2014). The results of this study show that there is a difference in the level of career anxiety between undergraduate and vocational students with a tailed sig.2 value of 0.000 <0.05 where vocational students have a higher level of career anxiety than undergraduate students.